Influence of scour depth and flow velocity field on large-diameter pier group pile foundations - Shi, Junfeng; Han, Changhai; Guo, Huijuan; Yu, Kaiwen; Han, Kang (Frontiers in Marine Science, 2024)
Sea-crossing bridges face critical challenges due to scour, which can destabilize foundations. This study investigates the scour characteristics of the large-diameter main pier of the Haiwen Bridge, with a pile diameter of 4.3 meters. Seabed changes were monitored over 630 days using field tests and numerical simulations. The study analyzed the relationship between flow velocity and scour depth, revealing that the maximum recorded scour depth was 3.65 meters at the upstream side. A linear regression model, developed from 75 sets of field data, produced a formula to estimate maximum local scour depth. Validation against field measurements showed a strong correlation, with the calculated values deviating by less than 10% from observed data. The findings indicate that upstream scour pits were 1.5 times wider and deeper than those downstream, while a shallow triangular scour zone, extending 1.2 times the pile diameter, formed downstream. Recommendations for scour protection include hydrological considerations, particularly on the upstream side and areas lacking sediment sources.